Uploaded on

 

More in: Technology
  • Full Name Full Name Comment goes here.
    Are you sure you want to
    Your message goes here
    Be the first to comment
    Be the first to like this
No Downloads

Views

Total Views
430
On Slideshare
0
From Embeds
0
Number of Embeds
3

Actions

Shares
Downloads
2
Comments
0
Likes
0

Embeds 0

No embeds

Report content

Flagged as inappropriate Flag as inappropriate
Flag as inappropriate

Select your reason for flagging this presentation as inappropriate.

Cancel
    No notes for slide

Transcript

  • 1. SOLVING QUADRATIC EQUATIONS USING THE QUADRATIC FORMULA April 15, 2014
  • 2. # 27. Change equation to the one on the board.
  • 3. You now possess 5 methods to solve quadratic equations. They are: C) Finding square roots B) Completing the square D) Creating a table of x/y values A) Factoring And thus, it is time. You have proven yourself and are ready for the awesome responsibility awaiting you.. You are about to acquire the ultimate weapon in your battle to slay the quadratic dragon. Ladies & Gentlemen, the nuclear option, the peace maker, the final solution... Beware though, it is wild and not easily tamed. E) Graphing
  • 4. **She’s beautiful, and she’s all yours The Quadratic Formula:
  • 5. THE QUADRATIC FORMULA .....Solves every quadratic equation, making ‘unsolvable’ a thing of the past. Imaginary numbers are not covered until Algebra 2. This means that we still may have some equations that are unsolvable to us. Pro’s Cons No figuring out what method to use Formula must be memorized If used every time, solving will be easier and faster Must always be aware of signs and order of operations
  • 6. Solve the equation with the Quadratic Formula 2x2 – 5x – 3 = 0 The first thing we need to do is to see if this fits the first formula. It does since it has the variable squared, the coefficient and the constant all equaling to zero. Next we find the a, b & c and put them into the second formula. a = 2 b = -5 c = -3
  • 7. EXAMPLE 1 x = 5 + 7 4 x = 12 4 x = 5 - 7 4 x = -2 4 x = 3 x = -1/2
  • 8. Rearrange to standard form first EXAMPLE 2 Solve 2x2 + 7x = 9 2x2 + 7x – 9 = 0 Identify the a, b & c and plug them in. 2x2 + 7x – 9 = 0
  • 9. Now we identify the a, b & c and place it in formula two. Then we solve. x = -(7) ± √(7)2 – 4(2)(-9) 2(2) x = -7 ± √49 – (- 72) 4 x = -7 ± √121 4 x = -7 ± 11 4 EXAMPLE 2
  • 10. x = -7 ± 11 4 x = 4 4 x = 1 x = -9/2 EXAMPLE 2 x = -7 - 11 4 x = -18 4 x = -7 + 11 4
  • 11. x = -(1) ± √(1)2 – 4(1)(-1) 2(1) LAST EXAMPLE Solve x2 + x – 1 = 0 First we need to identify a, b & c
  • 12. PROBLEM 3 x = -(1) ± √(1)2 – 4(1)(-1) 2(1) We can go no further since 5 can’t be squared. x = -1 + √5 2 x = -1 - √5 2 LAST EXAMPLE x = -1 ± √5 2 x = -1 ± √1+ 4 2
  • 13. COMPLETE & SUBMIT CLASS WORK TODAY!